Neutrophil Extracellular Traps (NETs) Promote Non-Small Cell Lung Cancer Metastasis by Suppressing lncRNA MIR503HG to Activate the NF-κB/NLRP3 Inflammasome Pathway - Wang, Yong; Liu, Fen; Chen, Lin; Fang, Chen; Li, Shuangyan; Yuan, Shangkun; Qian, Xiaoying; Yin, Yan; Yu, Biao; Fu, Biqi; Zhang, Xinwei; Li, Yong (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) that are produced in the tumour microenvironment (TME) have been suggested to play an essential role in the dissemination of metastatic cancer under multiple infectious and inflammatory conditions. However, the functions of NETs in promoting non-small cell lung cancer (NSCLC) metastasis and the underlying mechanisms remain incompletely understood. Here, we found that NETs promoted NSCLC cell invasion and migration by inducing epithelial to mesenchymal transition (EMT). To explore how NETs contribute to NSCLC metastasis, microarrays were performed to identify substantial numbers of long noncoding RNAs (lncRNAs) and mRNAs that were differentially expressed in NSCLC cells after stimulation with NETs. Interestingly, we observed that the expression of lncRNA MIR503HG was downregulated after NET stimulation, and ectopic MIR503HG expression reversed the metastasis-promoting effect of NETs in vitro and in vivo. Notably, bioinformatics analysis revealed that differentially expressed genes were involved in the NOD-like receptor and NF-κB signalling pathways that are associated with inflammation. NETs facilitated EMT and thereby contributed to NSCLC metastasis by activating the NF-κB/NOD-like receptor protein 3 (NLRP3) signalling pathway. Further studies revealed that MIR503HG inhibited NET-triggered NSCLC cell metastasis in an NF-κB/NLRP3-dependent manner, as overexpression of NF-κB or NLRP3 impaired the suppressive effect of MIR503HG on NET-induced cancer cell metastasis. Together, these results show that NETs activate the NF-κB/NLRP3 pathway by downregulating MIR503HG expression to promote EMT and NSCLC metastasis. Targeting the formation of NETs may be a novel therapeutic strategy for treating NSCLC metastasis.